Comparative effects of the aqueous leaf extract of ocimum basilicum and loperamide on intestinal transit in j rats (2006)
The effect of 10% aqueous leaf extract of Ocimum basilicum on intestinal transit in rats was determined and compared with that of loperamide (Imodium®), a known inhibitor of intestinal motility. Three doses of the leaf extract and loperamide were administered orally to the experimental rats, and the animals in the control group received 0.5 ml normal saline. Intestinal transit was measured in all the animals by the charcoal meal test and was expressed as the percentage of the distance traveled relative to the entire length of the intestine from the pyloric junction to the anal orifice. The mean transit point of dye in control rats was 66.68 ± 3.20%. The leaf extract of O. bacilicum caused a dose-dependent increase in the transit point. The mean transit points of the dye were 73.32 ± 3.77%, 74.84 ± 3.92% and 78.30 ± 4.30% at 0.5 ml/100 g body weight, 0.75 ml/100 g body weight and 1.0 ml/100 g body weight, respectively. Loperamide on the other band, caused a dose-dependent decrease in the transit point indicating reduced intestinal motility. For this drug, the mean transit points were 57.68 ± 2.50% at 0.10 mg/100 g body weight, 56.36 ± 4,78% at 0.20 mg/100 g body weight, and 50.95 ± 2.46% at 0.5 mg/100 g body weight. Loperamide and the leaf extract had opposing actions on the intestinal smooth muscle; while loperamide showed a constipating effect, O. basilicum aqueous leaf extract enhanced intestinal motility.